Pharmacotherapy in Aortic Disease - Evangelista, Arturo; Nienaber, Christoph A. (Current Cardiovascular Therapy, 2015)
This book is driven by the considerable progress made by novel imaging techniques in understanding the pathophysiology and evolution of aortic disease and its diagnosis. Despite the lack of symptoms in stable conditions, most aortic diseases have a high morbidity and mortality. New therapeutic strategies such as endovascular treatment and surgical techniques have appeared to improve conventional surgery in advanced phases of the disease, but until recently, medical treatment has focused on the control of cardiovascular risk factors using beta-blockers to reduce aortic wall stress by reducing blood pressure and heart rate. Pharmacotherapy in Aortic Disease updates the reader on the new medical treatment that are changing the natural history of these diseases. Leading experts have created a critical in-depth, yet concise, analysis of the available medical treatments for different aortic disease entities. Both basic research studies and clinical trials discussed in this book serve as a base for improving therapeutic management, delaying the need for surgery, and prolonging survival in these patients.